Konstruksi Identitas Budaya melalui Perkebunan: Studi Literatur terhadap Komunitas Aceh, Melayu, dan Tionghoa di Indonesia - Marzuti Isra; Nayla Rashifa; Ersandi Roihan Putra; Reza Syahputra; Rifadeo Rahmad Siregar; Fachry Pahlevi Siregar (Pusat Riset dan Inovasi Nasional, 2025)
This literature study examines the construction of cultural identity through socio-economic practices in plantation ecosystems among the Acehnese, Malay, and Chinese communities in Indonesia. Using a systematic literature review of 42 selected sources (1990-2023), the research reveals that plantations function as sites of identity negotiation—dynamic arenas of cultural adaptation and resistance. In Aceh, the integration of Islamic values (zakat [alms] from plantations, meunasah education) and local wisdom (peusijuek rituals) mediates post-conflict reconciliation and identity transformation from